3(x-2y)2-3x+6y
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/08 03:38:10
3(x-2y)2-3x+6y3(x-2y)2-3x+6y3(x-2y)2-3x+6y这个表达式都有问题,你咋个提出问题,0
3(x-2y)2-3x+6y
3(x-2y)2-3x+6y
3(x-2y)2-3x+6y
这个表达式都有问题,你咋个提出问题,
0
[2(x-y)^5-8(x-y)^2(x+y)+6y(x-y)^2]÷2(x-y)^2[2(x-y)^3-8(x-y)^2(x+y)+6y(x-y)^2]÷2(x-y)^2
3y/x*x-y*y+x/x*x-2xy+y*y+6y*y/x*x*x-x*x*y-xy*y+y*y*y等于多少?
因式分解3x^2(x-y)+6x(y-x)
【2(x-y)^3-8(x-y)^2(x+y)+6y(x-y)^2】/2(x-y)^2=
x(x-y)2-(y-x)3
[2/3x-2/x+y(x+y/3x-x-y)]/x-y/x
化简:{2/3x-2/(x+y)[(x+y)/3x-x-y]}/(x+y)/x
计算2/3x-2/x+y(x+y/3x-x-y)/x-y/x
化简3x-2/(x+y)[(x+y)/3x-x-y]÷(x-y)/x
2(2x+3y)(3x+2y)-(6x-y)(2x-5y)
x+y/2+x-y/6=5 2(x+y)-3(x-y)=-2
x+y/2+x-y/3=6,4(x+y)-3(x-y)=-20
{(x+y)/2+(x-y)/3=6 4(x+y)-3(x-y)=-20
4(x+y)-3(x-y)=-20,2/x+y+3/x-y=6
[12(x+y)^3+3(x+y)(x-y)^2]÷6(x+y)
4x-3y/x-2y÷6y-8x/y-2x
3(x-y)^2-7(x-y)+8(y-x)^2+6(y-x)合并同类项.
(x+y)/2- x-y/2=6 3(x+y)=4(x-y)